PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN DENGAN FINANCIAL CRISIS SEBAGAI VARIABEL MODERASI DAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MEDIASI - Hendri Budiman; Yulius Jogi Christiawan (Business Accounting Review, 2018)
This research was conducted to find out the influence of good corporate governance to firm performance with financial crisis as moderating variable and firm size as control variable. This study used a quantitative approach, which means the data obtained from financial statement published by companies listed in ISE. The data obtained from 384 companies in all sector in Indonesia in 2014 and 2016.The research results showed that there was positive and significant influence of board size toward firm performance. Board Independence had insignificant influence towards firm performance. Audit committee size had insignificant influence towards firm performance. Financial crisis showed positive and significant influence towards firm performance. Besides, financial crisis had insignificant influence as moderating variable to the influence of board size towards firm performance, the influence of board independence towards firm performance, and the influence of audit committee size towards firm performance. Firm size also showed insignificant influence towards firm performance.